Internal ribosomal entry site substitution eliminates neurovirulence in intergeneric poliovirus recombinants. - Gromeier, M (1996)
Neuropathogenicity of poliovirus can be attenuated by mutations in the internal ribosomal entry site (IRES) within the 5' nontranslated region of its genome. The Sabin vaccine strains used in prevention of poliomyelitis carry such mutations in their IRES elements. In addition, mutations within the structural and nonstructural proteins of Sabin strains may equally contribute to the attenuation phenotype. Despite their effectiveness as vaccines, the Sabin strains retain a neuropathogenic potential in animal models for poliomyelitis and, at a very low rate, they can cause poliomyelitis in vaccine recipients. The elimination of the neurocytopathic phenotype was achieved through the exchange of the entire poliovirus IRES with its counterpart from human rhinovirus type 2 without affecting growth properties in nonneuronal cells. The attenuating effect of the human rhinovirus type 2 IRES within the context of a poliovirus genome has been mapped to the 3' portion of this genetic element.